2019
DOI: 10.1111/1467-9566.12898
|View full text |Cite
|
Sign up to set email alerts
|

Understanding digital health: Productive tensions at the intersection of sociology of health and science and technology studies

Abstract: In this editorial introduction, we explore how digital health is being explored at the intersection of sociology of health and science and technology studies (STS). We suggest that socio‐material approaches and practice theories provide a shared space within which productive tensions between sociology of health and STS can continue. These tensions emerge around the long‐standing challenges of avoiding technological determinism while maintaining a clear focus on the materiality and agency of technologies and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 58 publications
1
43
0
1
Order By: Relevance
“…Scholarly research surrounding the use, benefits and impacts of digital technology in the lives of older citizens, as well as those of younger citizens (Ito et al, 2010;Cotten et al, 2014;Marston, 2019) has been growing over the last 30+ years (Czaja and Barr, 1989). The application of digital technologies in influencing social and psychological well-being have been widely studied with the focus of the types of digital connections and the intensities of using digital technologies among general population (Rosenfeld and Thomas, 2012;Hofstra et al, 2017;Verduyn et al, 2017;Rafalow, 2018;Henwood and Marent, 2019;Shah et al, 2019). The demographic profiles of the users, such as age, gender and education are important factors to understand the accessibility, frequencies and types of digital use in creating and enhancing social connections and support.…”
Section: Introductionmentioning
confidence: 99%
“…Scholarly research surrounding the use, benefits and impacts of digital technology in the lives of older citizens, as well as those of younger citizens (Ito et al, 2010;Cotten et al, 2014;Marston, 2019) has been growing over the last 30+ years (Czaja and Barr, 1989). The application of digital technologies in influencing social and psychological well-being have been widely studied with the focus of the types of digital connections and the intensities of using digital technologies among general population (Rosenfeld and Thomas, 2012;Hofstra et al, 2017;Verduyn et al, 2017;Rafalow, 2018;Henwood and Marent, 2019;Shah et al, 2019). The demographic profiles of the users, such as age, gender and education are important factors to understand the accessibility, frequencies and types of digital use in creating and enhancing social connections and support.…”
Section: Introductionmentioning
confidence: 99%
“…The paper is based on a UK study involving interviews with people who self-identified as monitoring their blood pressure or BMI/weight. Our engagement with selfmonitoring stemmed from our broader interest in everyday health practices, the use of health technologies in domestic settings and the way these might redistribute health work between the home and the clinic (see Henwood and Marent, 2019;Weiner et al, 2017;Weiner and Will, 2018;Williams et al, 2020, forthcoming). Home blood pressure monitoring and BMI monitoring offer particularly interesting cases in the way they blur the boundary between the clinic and the home.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the idea of curation helps to link the work of making data with the emotional aspects of self-monitoring and the value of the data. In our analysis, we adopt this lens to develop a socio-materialist account (Henwood and Marent, 2019;Weiner and Will, 2018;Williams et al, 2020, forthcoming) of everyday data practices relating to selfmonitoring, exploring what records people keep, what materials are involved and whether and how records are shared. We suggest that this curatorial approach helps to clarify the relationship between selfmonitoring and the accrual and flow of data.…”
Section: Curation As Socio-materials Practicementioning
confidence: 99%
“…At first glance, cyclic self-fashioning may be perceived as a reinforcement of biologism; however, I use this concept to explore how selftrackers bring particular "biopossibilities" into being (Willey 2016). My approach is situated in self-tracking scholarship that theorizes the body as a site for interpretation and challenges the singular conception of the neoliberal selftracking subject (Danesi et al 2020;Henwood and Marent 2019;Sharon 2015Sharon , 2016Weiner et al 2020). Consistent with a socio-material practice-based approach that emphasizes the ambivalence and fluidity of users' engagements with technologies, I take investigation of the role of biotemporal mediated entities in everyday life a step further, by focusing on practices that have received little attention in the literature so far.…”
Section: Introductionmentioning
confidence: 99%